2020
DOI: 10.1016/j.schres.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Common mechanisms for type 2 diabetes and psychosis: Findings from a prospective birth cohort

Abstract: Background Psychosis and type 2 diabetes mellitus (T2DM) are commonly comorbid and may share pathophysiologic mechanisms. To investigate shared genetic variation and inflammation as potential common mechanisms, we tested: (i) associations between genetic predisposition for T2DM and psychotic experiences and psychotic disorder in young adults; (ii) the association between genetic predisposition for schizophrenia and insulin resistance (IR), a precursor of T2DM; and (iii) whether these associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
2
10
0
Order By: Relevance
“…We identified a trend of positive genetic correlation between schizophrenia and a range of cardiometabolic and inflammation-related traits in the lowest MAF-quartile, though most results did not surpass the a priori determined Bonferroni significance threshold. This trend of results aligns with observational findings, 19 , 20 and also with studies using other methods to examine for genetic overlap between schizophrenia and cardiometabolic traits, eg analyses of GWAS pleiotropy, 40 polygenic risk score analysis, 38 transcriptomic and functional enrichment analysis, 41 and genetic colocalization analysis, 39 all of which reported evidence in support of genetic similarity between schizophrenia and cardiometabolic traits. We also identified a pattern of “cardioprotective” partial correlation in the highest MAF-quartile of schizophrenia with BMI and T2D, in line with whole-genome correlation estimates.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We identified a trend of positive genetic correlation between schizophrenia and a range of cardiometabolic and inflammation-related traits in the lowest MAF-quartile, though most results did not surpass the a priori determined Bonferroni significance threshold. This trend of results aligns with observational findings, 19 , 20 and also with studies using other methods to examine for genetic overlap between schizophrenia and cardiometabolic traits, eg analyses of GWAS pleiotropy, 40 polygenic risk score analysis, 38 transcriptomic and functional enrichment analysis, 41 and genetic colocalization analysis, 39 all of which reported evidence in support of genetic similarity between schizophrenia and cardiometabolic traits. We also identified a pattern of “cardioprotective” partial correlation in the highest MAF-quartile of schizophrenia with BMI and T2D, in line with whole-genome correlation estimates.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is inconsistent with observational studies suggesting increased T2DM risk in schizophrenia, 4 , 37 and studies reporting evidence of positive genetic overlap between schizophrenia and T2DM when using other genomic methods. 38–41 The observed partial negative correlation between schizophrenia and BMI could be one explanation for this, since T2DM and BMI are themselves highly genetically correlated. 42 Future research may seek to explore this in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent work from ALSPAC has found that genetic predisposition to type 2 diabetes was associated with an increased risk of psychosis at age 18 years, and vice versa; genetic predisposition to schizophrenia was associated with an increased risk of insulin resistance at age 18 years. 4 The study also found that the genotype-phenotype associations were mediated by inflammatory markers measured in childhood. These results indicate the potential for common underlying genetic mechanisms for comorbid psychosis and disrupted glucose-insulin homeostasis, which may involve genetic influences on inflammatory pathways.…”
Section: Factors Contributing To Childhood Immuno-metabolic Alteratio...mentioning
confidence: 86%
“…On the former, environmental adversity in early life through infection, stressful life events or malnutrition – each known risk factor for psychosis and cardiometabolic disorders – may permanently alter the immune system (Merlot et al ., 2008). On the latter, genetic predisposition to schizophrenia has been shown to associate with decreased cardiac volumes, increased ejection fractions and decreased absolute peak diastolic strain rates (Pillinger et al ., 2023) as well as other cardiometabolic traits including increased BMI (Bahrami et al ., 2020), insulin resistance (Perry et al ., 2022a) and type 2 diabetes (Perry et al ., 2020a).…”
mentioning
confidence: 99%